2008
DOI: 10.1016/j.neulet.2007.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent neurofunctional predictors of long-term maintenance of visual word learning

Abstract: A previous study has revealed sex-dependent neurofunctional predictors of visual word learning [C. Chen, G. Xue, Q. Dong, Z. Jin, T. Li, F. Xue, L. Zhao, Y. Guo, Sex determines the neurofunctional predictors of visual word learning, Neuropsychologia 45 (2007) 741-747]. The present study aimed to extend that study to investigate sex-dependent neurofunctional predictors of long-term maintenance. Twenty-three Chinese college students trained in the previous study were followed up twice: immediately (T1) and 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Spacing the repetitions of study materials reduced neural repetition suppression in the left midfusiform cortex and therefore increased the overall learning-related activity, and also enhanced the long-term memory of the novel characters. This corroborates our existing results [24], [25], [26] and further supports the important role of the midfusiform in learning and memorizing new characters. Interestingly, the midfusiform is found to be important for face memory [29], [58], which further challenges the VWFA hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Spacing the repetitions of study materials reduced neural repetition suppression in the left midfusiform cortex and therefore increased the overall learning-related activity, and also enhanced the long-term memory of the novel characters. This corroborates our existing results [24], [25], [26] and further supports the important role of the midfusiform in learning and memorizing new characters. Interestingly, the midfusiform is found to be important for face memory [29], [58], which further challenges the VWFA hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…Although many studies have revealed strong midfusiform activation when a novel script is being processed, the functional significance of the activity is not clear. One way to shed light on this issue is to investigate the connection between midfusiform activation and learning outcomes [24], [25], [26]. Whereas previous studies have found that midfusiform activation could predict subsequent episodic memory of familiar words [31], [32], [33], it is unclear whether such correlations would also be observed for novel characters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFG seed region, also known as the VWFA, was suggested for orthographic analysis, an early step in the reading process. Our previous studies revealed that both functional activity (indexed by activity) (Chen et al, 2007; Dong et al, 2008; Mei et al, 2010; Xue et al, 2006a; Xue et al, 2010) and structure (indexed by cortical thickness) (Zhang et al, 2013) of the FFG can predict reading ability and language learning in Chinese adults. The result from the current study suggests that reading ability is not only separately related to visual analysis and phonological processing, but also to the functional cooperation and connection between these two processes.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation of this overlap between native and second language’s neural networks is that the neural mechanisms for second-language processing are shaped by native language experience. In fact, some recent studies showed that the brain network shaped by native language experience is optimal for learning a new language (Chen et al, 2007; Dong et al, 2008; Mei et al, 2008; Xue et al, 2006a). …”
Section: Second-language Learningmentioning
confidence: 99%